More widespread than supposed: preserved lawsonite in the blueschist-facies ophiolitic bodies from the Albergian unit (Liguria-Piemonte zone, Western Alps) - Corno, Alberto; Mosca, Pietro; Groppo, Chiara; Borghi, Alessandro; Gattiglio, Marco (Ofioliti, 2022)
The Albergian unit (AU), belonging to the Liguria-Piemonte oceanic domain of the Western Alps, comprises a thick sequence of calcschists and minor meta-ophiolitic bodies, from metric to kilometric in size. The occurrence of fresh lawsonite in its metasedimentary cover is known since the end of the XIX century. This paper reports the occurrence of fresh lawsonite also in the metamafic rocks and presents petrological data to constrain the tectono-metamorphic evolution of one of these metamafic bodies exposed in the upper Chisone Valley. In the Monte Albergian - Gran Mioul area, the AU consists of a kilometric body of basalt and/or diabase metabreccias (with minor metagabbros and meta-plagiogranite clasts and blocks), covered by discontinuous layers of quartzitic metasandstones, black micaschists, and eventually a thick sequence of calcschists. This paper focuses on the petrographic and mineral chemistry features of these lithologies, with emphasis on the preserved magmatic textures in the metamafic clasts, and on fresh lawsonite occurrence and its replacement. The second part of the paper deals with phase equilibrium modeling of two representative samples from the area: a Mg-Al metagabbro and a metabreccia with plagiogranite clasts. Thermodynamic modeling of isochemical phase diagrams (i.e., P-T pseudosections), performed for the first time in this unit, allowed constraining the metamorphic peak in the lawsonite blueschist-facies conditions, at about 18-21 kbar and 380-430°C, followed by a partial re-equilibration in the epidote-stability field.